Turk Arch Pediatrics 2023
DOI: 10.5152/turkarchpediatr.2022.22141
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Levels in Children and Adolescents with Vasovagal Syncope, Syncope Due to Orthostatic Hypotension, and Cardiac Syncope

Abstract: Objective: The study aimed to compare vitamin D levels between children and adolescents with vasovagal syncope, syncope due to orthostatic hypotension, cardiac syncope, and healthy individuals and to investigate the correlations of 25(OH)D with main clinical parameters of syncope. Materials and Methods: This study involved 83 children aged 8-17 years with syncope: 40 with vasovagal syncope, 24 with syncope due to orthostatic hypotension, and 19 with cardiac syncope. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In line, it has been reported that 78.4% of Chinese children had vitamin D insufficiency 30 . Noteworthy, five of our included studies assessed children as their population while Kovalchuk et al found a rate of 60% deficiency ed in 40 children with VVS 14 . The main contributing risk factors causing vitamin D deficiency are vegetarian individuals, breastfeeding or pregnant women, less exposure to sunlight, and older adults with a higher prevalence of gastrointestinal and renal disease 25 …”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In line, it has been reported that 78.4% of Chinese children had vitamin D insufficiency 30 . Noteworthy, five of our included studies assessed children as their population while Kovalchuk et al found a rate of 60% deficiency ed in 40 children with VVS 14 . The main contributing risk factors causing vitamin D deficiency are vegetarian individuals, breastfeeding or pregnant women, less exposure to sunlight, and older adults with a higher prevalence of gastrointestinal and renal disease 25 …”
Section: Discussionmentioning
confidence: 71%
“…Moreover, Egger's and Begg's 22,23 Duplicates were removed (n = 89) and the remaining 365 went through the first screening using titles/abstracts after which 25 studies underwent full-text screening. Finally, six studies 14,15,[24][25][26][27] remained to be included in our systematic review.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations